2021
DOI: 10.1177/0308518x211053645
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrage spaces in the offshore world: Layering, ‘fuses’ and partitioning of the legal structure of modern firms

Abstract: In this article, we discuss the way offshore financial centres are used by the multi-subsidiary, multi-jurisdictional group structure known as the ‘multinational enterprise’ to arbitrage between social geographies of political jurisdictions. We define arbitrage as the use of corporate legal entities located in diverse jurisdictions to arbitrate a third country's rules and regulations. Using a new method to categorize firm-level data from Van Dijk’s Orbis, we operationalize the notion of arbitrage to systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Financial arbitrage based on legal provisioning is a crucial element in the article from Palan, Petersen and Phillips (2021). Drawing inspiration from Jean-Philippe Robé's work (2011, 2020), Palan and co-authors explore how firms, abetted by networks of accounting and law experts, have re-engineered their corporate structures to create ‘opportunity spaces’ in accommodative offshore sites, in which they realize and control a significant proportion of group profits.…”
Section: Transnational Legal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial arbitrage based on legal provisioning is a crucial element in the article from Palan, Petersen and Phillips (2021). Drawing inspiration from Jean-Philippe Robé's work (2011, 2020), Palan and co-authors explore how firms, abetted by networks of accounting and law experts, have re-engineered their corporate structures to create ‘opportunity spaces’ in accommodative offshore sites, in which they realize and control a significant proportion of group profits.…”
Section: Transnational Legal Managementmentioning
confidence: 99%
“…Social networks stabilize how actors in the market read one another, as well as create enduring relations and power asymmetries which shape markets. International legal structures provide avenues for arbitrage, ambiguity and absences (Grasten et al 2021), as well as the design of corporate structures to protect the interests – not of stakeholders – but the social unit of the firm (Robé 2020; Palan et al 2021). Below we extend this discussion of financial institutions, social networks and legal management as infrastructures that help us to understand the changes and continuities in the spatial organization of finance.…”
Section: Introductionmentioning
confidence: 99%
“…The second and related puzzle is that instead of concentrating exclusively on their supposedly core task of coordinating factors of production or developing mean, lean, efficient organizational structures, modern multinationals are creating ever-more complex networks of subsidiaries and affiliates held together by layers of holding entities (Palan et al, 2021; Phillips et al, 2021. A New York Federal Reserve Bank study found the number of subsidiaries and affiliates owned by some of the largest US banking holding companies rose to an average of 3,400 in 2012, up from about 1,000 in 1990 (Avraham, Selvaggi and Vickery, 2012).…”
Section: Introductionmentioning
confidence: 99%